Factors Influencing Investment Interest in Sharia Mutual Funds through the Bibit Application - Suryadi Alamsyah; Riskayanto; Siti Aisyah; Fikri Zaeni Hasbalah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Economic growth can be stimulated through increased public investment activities. The development of financial technology, such as the Bibit application, has facilitated access to investment, particularly in Islamic mutual funds. This study aims to analyze the influence of financial literacy, return perception, and risk perception on the investment interest of the Jabodetabek community through the Bibit application. This research employs a quantitative approach using primary data collected from 100 respondents through an online questionnaire with a non-probability sampling technique (snowball sampling). Data were analyzed using multiple linear regression with the assistance of SPSS, including classical assumption tests and hypothesis testing. The results indicate that financial literacy and return perception have a positive and significant effect on investment interest, while risk perception has a negative and insignificant effect. These findings suggest that improving financial knowledge and return expectations are key factors in enhancing public interest in investing in Islamic mutual funds through digital platforms.